Preludes to Modernism in Brazil - Lopez, Telê Ancona (ABEI Journal, 2002)
This study focuses on certain significant events in the years immediately preceding the Modern Art Week, the landmark in Brazilian Modernism, in 1922.These events open up what may be described as the first Modernist period, from 1917 to 1929, which could even be extended up to the Exhibition of 1931.